UN experts say treatment of Guantanamo detainees is 'inhuman and degrading' - News Wire (France 24, 2023)
With nearly constant surveillance, gruelling isolation and limited family access, the treatment of the last 30 Guantanamo detainees is "cruel, inhuman and degrading," UN rights experts said Monday as they reported on their first visit to the US military prison.
United States of America
Keywords: 2023-06 June